Gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS) – A Helicobacter-opposite point. (March 2021) - Tacheci, Ilja; Repak, Rudolf; Podhola, Miroslav; Benesova, Lucie; Cyrany, Jiri; Bures, Jan; Kohoutova, Darina
Abstract: Gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS) is a rare familial gastric cancer syndrome with an autosomal dominant pattern of inheritance. It is characterised by fundic gland polyposis of the gastric body and is associated with a significant risk of gastric adenocarcinoma. Unlike sporadic gastric cancer, Helicobacter pylori is usually absent in patients with GAPPS. This opposite-point finding has so far not been fully clarified. Prophylactic total gastrectomy is indicated in all cases of GAPPS with fundic gland polyposis and the presence of any dysplasia. If no dysplasia is found at histology, prophylactic gastrectomy is suggested at between 30 and 35 years of age, or at five years earlier than the age at which the youngest family member developed gastric cancer. Different phenotypes of GAPPS demand an individual approach to particular family members.